The Gendered Space of Capabilities and Functionings: Lessons from Haitian Community-Based Organizations. Issue 2 (3rd April 2018) - Vansteenkiste, Jennifer; Schuller, Mark
Abstract: Different frameworks for building capabilities result in different material outcomes for women in four Haitian community-based organizations: two mixed-gender versus two women's organizations. This study shows that frameworks deployed by the women's organizations pay attention to gendered strategic interests by enhancing capabilities and functionings that communities and individuals value. Their frameworks resembled Nussbaum's (2011, Creating Capabilities: The Human Development Approach . Cambridge: The Belknap Press of Harvard University Press): (1) practical reasoning and (2) affiliation, enabling combined capabilities and valued functionings in a manner that respects Sen's demands for plurality of individual freedoms within the society. We contend that when an organization makes gender central to a capabilities approach, space is created for women to imagine, practice, and choose real opportunities and functionings of value that are otherwise prohibited. This gendered capabilities methodology addresses political and social poverty and creates a platform for building democracy, offering a central frame scalable to national policy.